Sebuah analisis konflik dan manajemen risiko - Dwi Urip Wardoyo; Muhamad Fauzan Aziz; Sabrina Regita Dea Putri; Rifan Rizky Adisyahputra (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2023)
This study aims to find out how the development of accounting and the influence of accounting on conflict and risk management. The method used is literature review. The role of accounting with risk management in which the Company relies on external parties for greater risk financing than using its own internally generated funds. Market risk includes risk of foreign currency exchange rates and interest rates, as well as risk of commodity prices and equity.